Making the ‘Invisible’ Visible?: Reviews of Translated Works in the United Kingdom, France and Germany - Gray, Martyn P (2021)
In his 1995 seminal work, The Translator’s Invisibility, Lawrence Venuti examines the consequential impact of the reviewing of translations on the visibility of the translator. The American scholar contends that a fluent translation approach, which ultimately makes the work of the translator ‘invisible’ to the target reader, is the main criterion by which translations are read and assessed by reviewers; any deviations from such fluent discourse are dismissed as inadequate. The current research project takes its inspiration from Venuti’s comments and subsequent studies of reviewing practices and will thus examine the criteria by which translations are assessed in the United Kingdom, France and Germany. One of the aims of the project is therefore to either corroborate or contradict – or perhaps rather, update – Venuti’s assertions. However, it strives to be the most comprehensive research project into reviewing practices to date by introducing novel elements. For this reason, it is both a cross-cultural and cross-platform study: the thesis will assess not only how translations are reviewed differently in the three countries, but also how translations are reviewed depending on the popularity/specialisation of where the review is published in the year 2015. To achieve this, the project has three ‘points of attack’ for each country: popular corpora open for comments from the public, mainstream newspapers/supplements, and specialised literary magazines. Our journey through reviewing practices in each of the countries will demonstrate that, whilst fluency and transparency are still revered by many reviewers, the reviews in the corpus show a remarkable degree of openness towards diverse translation approaches. The thesis thus aims to call into question our understanding of the translator’s situation and activity in contemporary Western Europe and outlines the need for a redefinition of the very notion of the translator’s invisibility.